Distribution of Inherited Property Without the Application of Islamic Inheritance Law in Temanggung Regency - Mahzum Mahzum (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research examines the paradox of inheritance division without applying fikih mawaris in Temanggung Regency. The purpose of this study is to analyze how the practice of inheritance division that occurs in the Temanggung community runs without referring to the principles of fikih mawaris, as well as to explore the causes, impacts, and implications of this discrepancy on the applicable inheritance legal system. This research uses a qualitative approach with a case study method involving in-depth interviews with heirs, religious leaders, legal practitioners and the local community. The results show that although most Temanggung people have basic knowledge of Islamic inheritance law, the division of inheritance carried out often does not follow the provisions of fikih mawaris. This is due to the lack of understanding of fikih mawaris, the dominant influence of local customs, and the discrepancy between inheritance law practices and state legal regulations, especially in terms of the division of inheritance between children and wives. The implications of this mismatch create injustice in the distribution of inheritance, which is often detrimental to women and children from the wife's weaker position in society. This research suggests the need to record the division of inheritance in the village/kelurahan and even the existence of a deed of inheritance to be certain in handling cases of inheritance division without fikih mawaris.